Diversity of Toxic Chemical Substances Based on Viscera Report of Autopsy Samples Collected at Rajshahi Medical College in 2019 and 2020 - Uddin, Md Kafil; Uddin Gazi, Md Nasir; Talukdar, Sandwip; Raihan, Mir Md; Saha, Manasi; Shuvo, Samaunnur (TAJ: Journal of Teachers Association, 2022)
Objective: Investigation on autopsy samples is an urgent need to detect the presence of unwanted chemicals or toxins that could directly or indirectly cause death. This study was designed to analyze and explore the diversity of chemical substances that were found in the body of victims handled in the Department of Forensic Medicine & Toxicology (DFMT) at Rajshahi Medical College (RMC) in 2019 and 2020. Materials and Methods: The data were collected from the viscera report of the corresponding dead bodies submitted in DFMT at RMC for postmortem examination. Data analysis was performed using Microsoft Excel. Results: The most prevalent toxic agent was organophosphorus compounds which are usually being used as pesticides worldwide. The next most frequently used chemical was aluminium phosphide, a well-known poison. Conclusion: The findings of this study suggest producing and applying strict guidelines regarding supplying toxic chemical agents. TAJ 2021; 34: No-2: 43-47